ChemInform Abstract: Merging Visible‐Light Photoredox and Lewis Acid Catalysis for the Functionalization and Arylation of Glycine Derivatives and Peptides. Issue 14 (20th March 2013) - Zhu, Shaoqun; Rueping, Magnus
Abstract The reaction shows high functional group tolerance and applies glycine esters and glycine derived dipeptides as nucleophiles.